Influence of the Cement Dust on Ants Grouping (Hymenoptera, Formicidae) - Tetiana Mykytyn; Nelia Dolynko; Vasyl Stefurak; Natalia Bielova; Vasyl Kuzenko (Vasyl Stefanyk Precarpathian National University, 2020)
Research of the influence of cement dust in zone of PJSC "Ivano-Frankivskcement" on the ants grouping was conducted. In this exploration was noticed that at the anthropogenic load disappears ants of the genus Formica, which are replaced by species of the genus Lasius and Myrmica. Analyzing the distribution of ants genera and species on experimental meadows, we found a direct correlation between the ants number and distance from the sources of cement dust (r=0.87 at p<0.05). The largest number of the ant species observed in the area of influence from the genus Lasius. Myrmica nests are found not closer than 1 km from PJSC "Ivano-Frankivskcement", Formica nests are only in the control. Under the action of cement dust on biotopes, the ants display a non-adaptive reaction. The analysis of changes in the population density of the particular genera showed that the nests density of all genera is minimal on the meadows located near the sources of cement dust. With remoteness from the source of pollution, the density of colonies reliably increases (r=0,97 at p<0,05). Colonies of the genus Formica (F. fusca) registered only in control reached the density of grouping 1,5±1,1 nests at 100m the accounting route. For the forest biotopes, the nests density of the genus Lasius is higher in control by 1.8 times (3.1 nests/25 m2) than in the village (1.75 nests/25 m2). For other genera (Camponotus, Myrmica and Formica), an opposite reaction was registered. The nests density of F. fusca, which are registered only in the control, reached 2.5 ± 1.1 nests for 100 m the accounting route. With a decrease in the pollution degree, the proportion of underground nests increases (r=0,90 at p<0,05), the proportion of the dome nests decreases (r=-0,94 at p<0,05). At the same time, the size of dome on average decreases when removed from the source pollution. All nests registered in the most polluted zone consist of a mixture of cement dust and earths up to 45 cm high. About 75 % of all nests found were heavily overgrown. When excavating the nests the dome was as if cemented. Adaptation of the ants to the influence of cement dust differs from other influence types and is expressed in the fact that in technogenic territories nests are more often dome-shaped, smaller diameter and considerably higher nests than those located in the control zone. This is because the soil near PJSC "Ivano-Frankivskcement" is covered with a layer of the lime dust which reaches 5 cm. Lasius niger is resistant to various forms of the anthropogenic influence, which can be explained by the adaptive features of the forms ant nest.